Analisis Keterbacaan Petunjuk Praktikum Ekologi Perairan: Perspektif Mahasiswa - Widyantari, Rima; Lestari, Sofiana (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
This research aims to analyze the results of tests on the readability of aquatic ecology practical instructions. This type of research is descriptive qualitative. Data collection techniques use readability and documentation tests. The data analysis technique uses percentage techniques. The research results showed that the student readability test score was 84%. With this result, the aquatic ecology practical instructions that have been prepared are in the very good category and do not need to be revised.